A new method for continuous measurement of residence time distribution in spray drying. Issue 13 (3rd October 2022) - Ruprecht, Nora Alina; Köhler, Annette; Kohlus, Reinhard
Abstract: The residence time distribution of particles is one of the most important parameters during spray drying, since it directly impacts the thermal damage of a potential product. Due to insufficiencies of previous approaches for measuring the residence time distribution, a new method for continuous measurements was developed. This method simultaneously allows the determination of the residence time distribution of individual particle size fractions. The impact of air mass flow rate and particle size on the residence time distribution during spray drying was investigated. The mean particle residence time decreased with increasing air mass flow rate from 15.8 s for 190 kg/h, to 13.0 s for 210 kg/h and to 7.1 s for 230 kg/h, which is significantly shorter than the mean air residence time of 35.3 s, 31.9 s and 29.1 s, respectively. The mean particle residence time decreased with increasing particle size, with this effect being more pronounced for lower air flow rates. If the particle size is smaller than 105 µm, the presented technique can be transferred to any kind of single-stage spray dryer.